Chronic Brain Ischemia in Hypothyroisis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Endocrinopathy is one of the significant risk factors for cerebrovascular diseases. The number of such patients is constantly increasing in all economically developed countries of the world. Hypothyroidism is one of the most common endocrine diseases and is also an important medical and social problem.